Student Teacher Experiences of Learning and Pedagogical Involvement Using a Student-Centered Learning Approach - Arne Sørensen; Pål Lagestad; Hilde K. Mikalsen (MDPI AG, 2023)
To optimize students' levels of skills, knowledge, and competence in higher education, teachers have been encouraged to work systematically to understand how their pedagogical approaches affect the students' learning process and learning outcomes. The purpose of this study was to examine the efficacy of a student-centered learning design (SCL) in the subject of PE. A total of 24 PETE students were given the responsibility to create the schedule for their own education in a subject for a semester. During the semester, the students wrote reflections note on three occasions related to their learning process and learning outcome. The thematical analysis of the reflection notes revealed two main findings concerning the learning process: an invitation to participate and develop professional ownership, and mixed reflections on the need for teacher scaffolding. Furthermore, the analyses revealed two main findings concerning the learning outcome: improved learning and meaningful learning. Our findings indicate that students' participation, motivation, enjoyment, and learning outcomes increased due to the use of SCL as a pedagogical strategy. These findings are supported by other investigations, identifying SCL as a preferred strategy according to students' learning process and learning outcomes. The main pedagogical implication of our findings is a recommendation to implement SCL as a pedagogical strategy for student learning in teacher education.